PENGARUH PROBLEM BASED LEARNING TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Fitri Nuryanah; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2015)
The objective of this research was to know the influence of PBL in improving students activities and learning outcomes. This research was experiment study with pretest-posttest nonequivalent. The samples of this research were the students at class X4 and X6 that were chosen by purposive sampling technique. The quantitative data were obtained from pretest, posttest, and N-gain score which was analyzed by using t-test and U-test with the support of SPSS 17 in 5% confidence levels. The qualitative data were description of student activities using PBL model. The result of students learning activities was in average of high criteria. For the asking question skill was 58,3%; collecting data was 86,7%; presented the results of the discussion was 75%; and giving an opinion was 90%. The result of students learning has increased with the average N-gain was 45. Thus, PBL model was effected on students activities and significant on result.Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh PBL terhadap aktivitas dan hasil belajar siswa. Penelitian ini merupakan studi eksperimen dengan desain pretes-postes tak ekuivalen. Sampel penelitian adalah siswa kelas X4 dan X6 yang dipilih secara purposive sampling. Data kuantitatif diperoleh dari nilai pretes, postes dan N-gain yang dianalisis secara statistik menggunakan uji-t dan uji-U pada taraf kepercayaan 5% dengan bantuan program SPSS 17. Data kualitatif berupa deskripsi aktivitas siswa terhadap penggunaan model PBL. Hasil aktivitas belajar siswa rata-rata berkriteria tinggi. Pada aspek kemampuan mengajukan pertanyaan 58,3%; Mengumpulkan data 86,7%; mempresentasikan hasil diskusi 75%; dan menyampaikan pendapat 90%. Hasil belajar berpengaruh signifikan dengan rata-rata N-gain 45. Dengan demikian model PBL berpengaruh terhadap aktivitas dan signifikan terhadap hasil belajar siswa.Kata kunci : aktivitas belajar siswa, hasil belajar siswa, problem based learning